Everyday spaces the potential of neighbourhood space - Gallacher, Pauline (Thomas Telford, 2005)
This text looks at the origins and aspirations of innovative public space, based on a particular project unique for its time. It reveals a general lack of focus on the issue of public space in ordinary neighbourhoods, in contrast to the increasing amount of attention devoted to city centre locations.